Penuntutan Terhadap Pelaku Tindak Pidana Penyalahguna Narkotika Di Luar Golongan Yang Di Atur Dalam Lampiran Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Syafruddin Kalo; Mahmud Mulyadi; Edy Ikhsan; Fahri Rahmadhani (Iuris Studia: Jurnal Kajian Hukum, 2021)
Law is a social engineering. In order to enforce legal function as a means of social engineering, a law should be transparent toward social dynamics in society. One of the legal fields which is closely related to social life is criminal law. One of the types of crime which is fully concerned by criminal jurisprudence today is criminal act in narcotics. The development in science and technology has caused criminal act in narcotics to be difficult to handle such as the new type of narcotics, Methylene (3,4 Methylenedioxy Metkatinon) which has recently been talked about since Raffi Ahmad case came to the fore; it is not registered in the Appendix of Law No. 35/2009 on Narcotics. The objective of the research was to find out legal provisions, laws, and regulations on narcotics which exists in Indonesia, to find out the prosecution on criminal act in narcotics abuse outside the classification stipulated in Law No. 35/2009, and to find out the obstacles in the prosecution on criminal act in narcotics outside the classification stipulated in Law No. 35/2009. The research used judicial normative and descriptive analytic method. The result of the research showed that the national legal products on criminal act in narcotics were stipulated in Law No. 9/1976 on Narcotics, Law No. 22/1997 on Narcotics, and Law No. 35/2009 on Narcotics. Methylene has chemical structure which resembles ecstasy, but it has great impact; it cannot even be used for medical and cosmetics. The enforcement of criminal law on methylene abuse can be done by legal finding through interpretation. Interpretation method is done in systematical, doctrinaire, teleological, and extensive way. However, interpretation should be done limitedly. The obstacles in prosecuting criminal act in narcotics outside the classification stipulated in Law No. 35/2009 can be viewed from the factors of law, law enforcement, facility and infrastructure in enforcing law, society, and culture. It is recommended that the Minister of Health issue a regulation on the amendment of the Narcotics Classification. Law enforcement, particularly public prosecutors, should dare to make a breakthrough in the case of methylene (3,4 Methylenedioxy Metkatinon) because by interpreting this derivative compound judicially, it can be made similar to cathinone in the list of the Appendix of Law No. 35/2009 on Narcotics